2011
DOI: 10.1159/000325731
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperfusion Treatment in a Septic Shock Patient with Autosomal Dominant Polycystic Kidney Disease and Increased HMGB1 Protein Levels

Abstract: This case report describes polymyxin B-immobilized fiber (PMX-F) treatment of septic shock caused by pyelonephritis in a 68-year-old woman with autosomal dominant polycystic kidney disease. She was admitted for severe lower left abdominal pain, high fever (40°C) and gross hematuria. Her endotoxin and high-mobility group box-1 protein (HMGB1) levels were extremely elevated. Her blood pressure was 68/36 mm Hg. Urinalysis revealed innumerable white blood cells (WBCs). Blood and urine cultures were positive for Kl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Recently, increasing numbers of studies have reported that the RAGE ligands and their stimulatory signals are highly increased in ADPKD. These include the HMGB1, for which high secretion was noted in the serum of ADPKD patients with septic shock or hypertension (19, 20). In addition, S100A8 and S100A9 were previously found to be highly expressed in cyst‐lining epithelial cells, as observed in Pkd2 transgenic mice, one of the ADPKD rodent models with polycystic kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing numbers of studies have reported that the RAGE ligands and their stimulatory signals are highly increased in ADPKD. These include the HMGB1, for which high secretion was noted in the serum of ADPKD patients with septic shock or hypertension (19, 20). In addition, S100A8 and S100A9 were previously found to be highly expressed in cyst‐lining epithelial cells, as observed in Pkd2 transgenic mice, one of the ADPKD rodent models with polycystic kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Serum HMGB1 level is increased and correlates with oxidative stress status in autosomal dominant polycystic kidney disease (Nakamura et al, 2011a; Nakamura et al, 2012a). …”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…Autosomal dominant polycystic kidney disease (ADPKD) is the most common monogenic kidney disease and the fourth leading cause of end-stage kidney disease in adults worldwide (42). Recently, two research groups reported that the serum level of HMGB1 was increased in ADPKD patients (43,44) which suggests that HMGB1 may play a role in ADPKD.…”
Section: Hmgb1 and Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 99%